Challenges of in vitro characterization of nonbiological complex drugs: Example of parenteral preparations with liposomal drug carriers - Krajišnik Danina; Milić Jela; Savić Snežana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
A greater variety of pharmaceutical preparations can be administered by the parenteral route, the composition of which can be simple (aqueous solutions) and more or less complex (emulsions, suspensions, liposomes as carriers of active pharmaceutical ingredients, particle systems, solid implants/implants). In addition, advances in bioand nanotechnology have enabled the development of new classes of complex drugs, so-called non-biological complex drugs (and their similars) whose further development is expected in the near future, and which are in many cases applied by parenteral route. Parenteral preparations containing active substances encapsulated in the liposome-type carriers represent a class of non-biological complex drugs which have the longest use so far and whose properties and defined quality characteristics are being most examined. In this paper, an overview of mandatory and additional (specific) in vitro tests for parenteral liposomal drug carriers is presented. The fact that standard testing procedures are often not available in relevant pharmacopoeias (Ph. Eur., USP and JP), so that they can vary significantly between laboratories, contributes to the great variability of the results obtained and constraints in their mutual comparison. EMA and FDA, as regulatory agencies, have also participated in the preparation of certain documents and development of appropriate standards and guidelines for quality control of liposomal drug carriers for parenteral application.